2005
DOI: 10.2527/2005.8392215x
|View full text |Cite
|
Sign up to set email alerts
|

Use of ear tags and injectable transponders for the identification and traceability of pigs from birth to the end of the slaughter line1,2

Abstract: A total of 557 newborn piglets were used to compare eight identification devices, including one plastic ear tag as a control (C, n = 348) and two types of electronic ear tags (E1, n = 106; and E2, n = 103), and five types of injectable transponders (n = 557): small 12-mm (D12, n = 116; and S12, n = 110), medium 23-mm (T23, n = 108), and large (32-mm, T32, n = 115; and 34-mm, S34, n = 108). Injections were made s.c. in the auricle base (n = 248) and intraperitoneally (n = 309) using a new technique. All piglets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
8
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 12 publications
6
45
8
1
Order By: Relevance
“…Although ear tags were the main identification system used for breeding stock among producers, concerns such as tag losses and reading difficulty, which have been previously reported in different studies evaluating plastic ear tag performance (Caja et al, 2005;Schembri et al, 2007a), were raised. Progeny were identified mainly for litter identification using ear notches or ear tattoos, and consequently no individual identification was used.…”
Section: Discussionmentioning
confidence: 99%
“…Although ear tags were the main identification system used for breeding stock among producers, concerns such as tag losses and reading difficulty, which have been previously reported in different studies evaluating plastic ear tag performance (Caja et al, 2005;Schembri et al, 2007a), were raised. Progeny were identified mainly for litter identification using ear notches or ear tattoos, and consequently no individual identification was used.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have considered the impact of identification procedures on animal welfare (Leslie et al, 2010). Electronic identifiers used in pigs include injectable transponders (Lambooij, 1992;Merks and Lambooij, 1990;Hernández-Jover et al, 2003) and transponders integrated in ear tags (Caja et al, 2005). The most suitable injection sites, in relation to transponder size, are the auricle base and the auricle.…”
Section: Introductionmentioning
confidence: 99%
“…The most suitable injection sites, in relation to transponder size, are the auricle base and the auricle. Results obtained in different experiments showed that injectable transponders in the intraperitoneal position are suitable too (Caja et al, 2005;Babot et al, 2006) and easily removable avoiding carcass contamination. One drawback related to the intraperitoneal site is the complexity of the injection itself, which requires specific training.…”
Section: Introductionmentioning
confidence: 99%
“…A mobile embedded sensor does not control its movement as it is attached or placed in the target. In animal management, it is usually tethered on to the animal [14], placed in the animal rumen [13], or inserted under the animal skin [26]. Finkenzeller [27] indicates that there are four types of transponders that can be affixed to an animal, including collar mounted transponders, ear tags, injectable transponders, and rumen bolus transponders.…”
Section: Mobile Embedded Sensor Nodementioning
confidence: 99%